STRATEGI PENGELOLAAN TERUMBU KARANG DENGAN PENDEKATAN TRANSPLANTASI DI PULAU SAMALONA - Muhammad Fuad Haris Ramdani; Abdul Rauf; Hamsiah Hamsiah; Arwin Arwin (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
Samalona Island, located in Makassar City, is a marine tourism destination with a high diversity of coral reefs. However, human activities and environmental degradation have caused damage to much of the reef ecosystem. This study aims to: (1) analyze the growth rate and survival of corals in rehabilitated areas, (2) identify the inhibiting factors for coral growth, and (3) formulate a management strategy based on rehabilitation. The method used is the Underwater Visual Census (UVC) with spider web-shaped transplant media. Primary data were collected through direct observation, while secondary data were obtained from related agencies. The findings indicate that coral transplantation can support ecosystem recovery when proper methods, location selection, and regular monitoring are implemented. This study provides strategic recommendations for sustainable coral reef management involving local community participation and integrated marine conservation.